Dampak Globalisasi Perdagangan Terhadap Tingkat Kesejahteraan Negara-negara Berpenduduk Muslim - Hikmatul Aliyah; I. Indra (Faculty of Economic and Business, 2017)
The Impact of Trade Globalization on Welfare in Moslem CountriesThis study aims at examining the impact of trade globalization on walfare level in the Moslem countries. Our welfare variable was measured using maqashid sharia approach, namely care of religion (proxied by conflict intensity), care of the soul (proxied by death rate), care of intellect (proxied by education participation rate), care of the offspring (proxied by population rate) and care of the treasure (proxied by GDP per capita). Meanwhile, trade globalization was proxied by trade openness. In addition to completed analysis, we also employed inflation and exchange rate as additional control variables. Our empirical model used panel data model consisting 9 moslem countries over 1980-2011. This study verified that trade openness has significantly positive effect on welfare indicators, such as population rate, education participation rate, GDP per capita, and death rates decline in the Moslem countries. Our estimation also found that inflation and exchange rate appear to be significantly affecting almost all welfare indicators used in analysis.DOI: 10.15408/ess.v7i1.4764